Knowledge of cervical cancer risk factors among Palestinian women: a national cross-sectional study - Mohamedraed Elshami; Mariam Thalji; Hanan Abukmail; Ibrahim Al-Slaibi; Mohammed Alser; Afnan Radaydeh; Alaa Alfuqaha; Salma Khader; Lana Khatib; Nour Fannoun; Bisan Ahmad; Lina Kassab; et al. (BMC, 2021)
Abstract Background High awareness of cervical cancer (CC) risk factors is important to decrease the morbidity and mortality associated with CC. This study aimed to assess the knowledge level of Palestinian women about CC risk factors and to determine the factors associated with good knowledge. Methods This was a national cross-sectional study. Adult women from hospitals, primary healthcare centers, and public spaces of 11 governorates in Palestine were recruited using a stratified convenience sampling. A translated-into-Arabic version of the validated CC awareness measure (CeCAM) was used to assess the knowledge about the 11 CC risk factors. For each correctly identified risk factor, the participant was given one point. The total score was calculated and was categorized into three categories: poor knowledge (0-3), fair knowledge (4-7), and good knowledge (8-11). Results A total of 7223 participants completed the Arabic CeCAM (response rate = 89.3%) and 7058 questionnaires were included in the final analysis: 2655 from the Gaza Strip and 4403 from the West Bank and Jerusalem. Participants recruited from the Gaza Strip were younger, getting lower monthly incomes, and with less chronic diseases than participants recruited from the West Bank and Jerusalem. The most frequently identified risk factor was 'having a weakened immune system' (n = 5458, 77.3%) followed by 'infection with a sexually transmitted infection' (n = 5388, 76.3%). The least identified risk factor was 'having many children' (n = 1597, 22.6%). Only 1670 women (23.7%) had good knowledge of CC risk factors. Women living in the Gaza Strip were more likely than women living in the West Bank and Jerusalem to have good knowledge (25.2% vs 22.7%). Completing a secondary or diploma degree, being employed, and having a monthly income of ≥ 1450 NIS (around $450) were all associated with lower likelihood of having good knowledge of CC risk factors. Conversely, knowing someone with cancer was associated with higher likelihood of having good knowledge. Conclusion The overall awareness of CC risk factors was low. There is a substantial need to establish educational programs to promote Palestinian women's awareness of CC.